How Did 9/11 Affect Terrorism Research? Examining Articles and Authors, 1970–2019 - Phillips, Brian J. (Terrorism and political violence, 2023)
Terrorism research increased markedly after the attacks of September 11, 2001 (9/11). How has research on this subject changed in the past twenty years? I examine data on more than 6,000 academic articles on terrorism between 1970 and 2019, and the more than 1,500 authors of multiple articles. This information comes from every article in the Web of Science database with “terrorism” or “terrorist” in the title. Several primary findings emerge. (1) The volume of terrorism research surged to record highs after 9/11, and has not decreased since. (2) Psychologists became the most numerous terrorism researchers after 9/11, displacing political scientists for about ten years. Research on health or medical aspects of terrorism jumped after 9/11. (3) The proportion of female scholars increased substantially after 9/11, outpacing the rise in academia generally. This is in part because scholars new to the field were often from disciplines with relatively high percentages of women, such as psychology. (4) Terrorism scholars were mostly based in North America or Western Europe before 9/11, but the number of countries with scholars publishing terrorism research expanded considerably after 2001. Overall, terrorism research has developed in many ways over the decades, but 9/11 led to fundamental changes.